Saving behaviors of private households under varying tariff structures, price levels and incentives - Experimental evidence - Franziska Harpenau; Katrin Marques Magalhaes; Nico Steffen; Lukas Wiewiorra (WIK Wissenschaftliches Institut für Infrastruktur und Kommunikationsdienste, 2023)
More efficient and sustainable energy consumption behaviors are crucial to mitigate the adverse effects of climate change. This paper examines how dynamic personal pricing and externality cost incentives interact and affect energy conservation behaviors. We conduct an online lab experiment in which participants complete real-effort tasks under different cost schemes. Increasing personal costs that reduce individual bonuses, significantly decreases participants' energy usage, although it requires more effort in the form of additional time. However, emphasizing increases in externality costs, representing environmental damage through reduced donations, does not impact performance. This suggests that the introduction of such prosocial incentives matters more than their magnitude. While environmental attitudes predict baseline usage, they do not change marginal responses to cost changes. Our results provide novel evidence on the motivational nuances underlying energy conservation and have key implications for policies considering a combination of incentives. – – Ein effizientes und nachhaltiges Energiesparverhalten ist von zentraler Bedeutung, um die negativen Auswirkungen des Klimawandels abzumildern. In diesem Beitrag wird untersucht, wie dynamische Anreize von Preisen und Externalitäten zusammenwirken und das Energiesparverhalten beeinflussen. Wir nutzen ein Online-Laborexperiment, bei dem die Teilnehmenden "Real-effort" Aufgaben unter verschiedenen Kostenstrukturen lösen. Eine Erhöhung der Kosten, welche individuelle Boni reduzieren, führt zu einem signifikanten Rückgang des Energieverbrauchs der Teilnehmenden, was aber mehr Aufwand in Form von zusätzlicher Zeit erfordert. Allerdings hat die Kommunikation steigender Externalitätskosten - die eine Spende verringern und Umweltschäden simulieren - keine Auswirkungen auf das Verhalten im Experiment. Dies deutet darauf hin, dass die Einführung solcher prosozialer Anreize wichtiger ist als deren Höhe. Während umweltfreundliche Einstellungen den grundsätzlichen Energieverbrauch beeinflussen, ändern sie hier nicht die marginalen Reaktionen auf Kostenänderungen.
Keywords: Q41; Q56; D91; 330; Energy consumption; Energy conservation; Behavioral; Environment